Characterization of pervious concrete focusing on non-destructive testing - MARTINS FILHO,S. T. (2020)
Abstract This study aims to investigate the properties of pervious concrete focusing on characterization tests by the Ultrasound Method. For this, three mixtures were produced with the paste/aggregate (P/Ag) ratio ranging from 0.45 to 0.65, water to cement ratio (w/c) of 0.3, and all the specimens were compacted with a steel rod. The application of the ultrasound method deserves special attention for the characterization of pervious concrete, due to a lack of research and the potential to develop analytical models for predicting properties from ultrasonic pulse velocity (UPV) as an independent variable. The UPV obtained in this study ranged from 3642 to 4262 m/s for an approximately 12% reduction in porosity, with a correlation (R²) of 0.91. It is noteworthy that the high porosity of pervious concrete causes attenuation of the ultrasonic wave. The measurements of UPV had higher values for specimens with higher densities (R²=0.87), higher compressive and tensile strengths (R² of 0.79 and 0.84, resp.), and lower permeability (R² = 0.91).